Non-tuberculous mycobacteria: occurrence in skin test cattle reactors from official tuberculosis-free herds - Gomez-Buendia, Alberto; Alvarez, Julio; Bezos, Javier; Mourelo, Jorge; Amado, Javier; Saez, Jose Luis; de Juan, Lucia; Romero, Beatriz (Frontiers in Veterinary Science, 2024)
Non-tuberculous mycobacteria (NTM) are considered a relevant cause of non-specific reactions to the most widely applied bovine tuberculosis (bTB) test, the intradermal tuberculin test. In order to establish which NTM species might act as a potential source of such diagnostic interference, a collection of 373 isolates obtained from skin test positive cows from 359 officially tuberculosis-free (OTF) herds, culled in the framework of the bTB eradication campaign in Spain, were identified at the species level through PCR and Sanger sequencing of the 16S rDNA, hsp65 and rpoB genes. Of the 308 isolates for which a reliable identification was achieved, 32 different mycobacterial species were identified, with certain species being most represented: among M. avium complex members (n = 142, 46.1%), M. avium subsp. hominissuis (98; 69.0%) was the most abundant followed by M. avium subsp. avium (33, 23.2%), M. intracellulare (7, 4.9%). Among non-MAC members (n = 166, 53.9%), M. nonchromogenicum (85; 27.6%) and M. bourgelatii (11; 5.6%) were the predominant species. In addition, mixed results were obtained in 53 isolates presenting up to 30 different genotypes, which could be indicative of new mycobacterial species. Our results represent a first step towards characterising the diversity of NTM species that could interfere with official diagnostic tests for bTB eradication in Spain.